Artistic ambivalence in clay : portraits of pottery, ceramics, and gender - Weida, Courtney Lee (Cambridge Scholars, 2011)
This book is a collection of glimpses into the lives and works of fifteen prominent women artists in contemporary ceramics. Spanning multiple genres, generations, and geographies, these potters and ceramic sculptors describe nuances, contradictions, and tensions surrounding their artworks, artistic processes, and professional lives. Otherin this text, artistic ambivalences are questioned and analyzed in terms of myriad gender issues. Featured ceramicists include: Maureen Burns-Bowie, Esta Carn ...